Different aspects of lactation persistency in dairy cows - TORSHIZI, MAHDI ELAHI; MASHHADI, MOJTABA HOSSEINPOUR; FARHANGFAR, HOMAYOUN (The Indian Journal of Animal Sciences, 2019)
Lactation persistency (cow’s ability to maintain milk production after reaching its peak) is a very important economic characteristic in the dairy cattle production system. Different definition and functions for describing and measuring of this trait were proposed by researchers. The random regression model using Legendre polynomial was one of the common and effective methodologies for evaluation of persistency in the last decade. Several factors affecting persistency such as different characteristics of lactation curve, environment factors, reproduction traits and health status of the dairy cow. Based on different studies the heritability of this trait was low to medium and negative or positive amount of genetic correlation between persistency and total milk yield in dairy cattle is attributed to persistency measures and method of data analysis. Persistency is related with low and later peak yield and selecting cows for peak yield will improve persistency and lactation curve traits. Analysis of relationships between persistency and other functional traits show signs that genetic improvement for persistency is possible and favorable. Different aspects and relationships of persistency with various lactation and other functional traits in dairy cows are reviewed in this article.